Silicon compatible acoustic wave resonators: design, fabrication and performance - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin (IIUM Press, 2014)
Continuous advancement in wireless technology and silicon microfabrication has fueled exciting growth in wireless products. The bulky size of discrete vibrating mechanical devices such as quartz crystals and surface acoustic wave resonators impedes the ultimate miniaturization of single-chip transceivers. Fabrication of acoustic wave resonators on silicon allows complete integration of a resonator with its accompanying circuitry. Integration leads to enhanced performance, better functionality with reduced cost at large volume production. This paper compiles the state-of-the-art technology of silicon compatible acoustic resonators, which can be integrated with interface circuitry. Typical acoustic wave resonators are surface acoustic wave (SAW) and bulk acoustic wave (BAW) resonators. Performance of the resonator is measured in terms of quality factor, resonance frequency and insertion loss. Selection of appropriate piezoelectric material is significant to ensure sufficient electromechanical coupling coefficient is produced to reduce the insertion loss. The insulating passive SiO2 layer acts as a low loss material and aims to increase the quality factor and temperature stability of the design. The integration technique also is influenced by the fabrication process and packaging. Packageless structure using AlN as the additional isolation layer is proposed to protect the SAW device from the environment for high reliability. Advancement in miniaturization technology of silicon compatible acoustic wave resonators to realize a single chip transceiver system is still needed